Penentuan Jumlah dan Kombinasi Jenis Kendaraan dengan Saving Heuristik pada Perusahaan Jasa Logistik Pihak Ketiga - Rusdiansyah, Ahmad; Aryusamalia, A (Jurnal Teknik Industri, 2007)
PT XYZ is company of logistics service of PT CI where this company hold responsible to logistics activity of PT CI that is covering distribution and warehousing. In transportation activity PT XYZ conducted armada outsourcing transport from some transporter every day. A problem faced in this time was truck rent expenses for the delivery of order to store. Hypothesis customer early from this research was if it done consolidation delivery of order customer, hence expected will be yielded to decrease cost rent daily truck which enough significant. At this research, consolidation conducted by developing method of saving heuristic. By using data of customer was same order on February, 10 2006, this research can reduce consumer of truck counted 3 truck and yield cost-saving rent equal to 18.87% from expense of early. This research also design software prototype for daily operational activities in determining used truck.